2014
DOI: 10.4028/www.scientific.net/amm.474.153
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis and Simulation of Drawpiece Forming Process by Finite Element Method

Abstract: This paper shows the application of an incremental modelling and numerical solution of the contact problem between movable elastic or rigid tool and elastic/visco-plastic bodies developed in [ to the numerical simulation of drawpiece forming process for the case of rigid tool (punch and die block) and elastic-plastic body (drawpiece). Also the current state of knowledge of the subject matter of the drawing process, modelling and simulation of this process is discussed. The latest and unconventional methods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…It can be observed that the values of the equivalent stress at the periphery of the disc after removing the elastic strain is almost 3 times reduced. Figure 5 shows a cross-sectional view of a discrete model of the drawing process (Kaldunski and Kukielka, 2014). The die which is used has rounding radius r d = 16 mm and internal diameter d = 40 mm.…”
Section: Numerical Model and Resultsmentioning
confidence: 99%
“…It can be observed that the values of the equivalent stress at the periphery of the disc after removing the elastic strain is almost 3 times reduced. Figure 5 shows a cross-sectional view of a discrete model of the drawing process (Kaldunski and Kukielka, 2014). The die which is used has rounding radius r d = 16 mm and internal diameter d = 40 mm.…”
Section: Numerical Model and Resultsmentioning
confidence: 99%
“…The concept of incremental description has already been verified by the author and was used to describe other plastic-forming processes: cutting [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ], thread rolling [ 15 , 16 , 17 , 28 , 29 ], burnishing rolling [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ], drawing [ 50 , 51 , 52 ], grinding with a single abrasive grain [ 53 ], calculating the fatigue strength of products [ 54 , 55 , 56 ], and diamond sliding burnishing [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…As a result, for successive discrete moments of time τ 0, Δt, 2Δt, … the geometry of the body and the states of incremental displacements, displacement velocities, accelerations, strains, strain rates, and stresses are determined. The concept of incremental description has already been verified by the author and was used to describe other plastic-forming processes: cutting [36][37][38][39][40][41][42], thread rolling [15][16][17]28,29], burnishing rolling [43][44][45][46][47][48][49], drawing [50][51][52], grinding with a single abrasive grain [53], calculating the fatigue strength of products [54][55][56], and diamond sliding burnishing [56].…”
Section: The Concept Of Incremental Descriptionmentioning
confidence: 99%
“…A further advantage of AWJ technology is its environmental friendliness, since amid the known treatment method of machining only plastic processing [ 11 , 12 ] and AWJ cutting [ 13 , 14 ] can stand up to these requirements.…”
Section: Introductionmentioning
confidence: 99%